The unmet needs in management, the treatment gap and the burden of migraine in Greece: a Delphi consensus and focus group study from patients’ perspective - Vikelis, Michail; Kourlaba, Georgia; Barba, Lia; Bilias, Konstantinos; Barbalia, Elena; Solakidi, Argyro; Trafalis, Dimitrios; Lioliou, Katerina; Zyga, Sofia; Karapanayiotides, Theodoros; Mitsikostas, Dimos-Dimitrios (Frontiers in Neurology, 2025)
IntroductionMigraine is a chronic, debilitating neurological disease affecting more than 1 billion patients, worldwide. Even though migraines are not life-threatening, they have profound effects on individuals, families, and society.ObjectiveThe aim of this study was to describe patients’ perspectives on socioeconomic and humanistic burden of migraine, as well as the unmet medical needs in the clinical management of migraine, in Greece.MethodsA mixed study design of a Delphi panel and a focus group was conducted, in which 16 and 9 episodic migraine patients from the two Greek migraine patient associations participated, respectively. A structured questionnaire of 45 statements regarding burden of disease diagnosis, treatment and unmet needs was used to collect data at Delphi consensus panel. An open and balanced discussion with all participants took place, under the co-ordination of one moderator during the focus group. At each round of the Delphi panel, the percentage of participants who responded “Agree/Strongly Agree,” “Disagree/Strongly disagree” and “Neither Agree nor Disagree” was calculated. The consensus threshold was set at 70% of responses. A thematic analysis was performed for the focus group.ResultsConsensus was achieved on 34 out of 45 statements. Thematic analysis revealed that patients face severe problems at work due to a lack of understanding and awareness of migraine burden from colleagues and employees, they are forced to modify their daily activities to avoid migraine attacks, and they experience prolonged diagnostic and treatment journey since they visit different medical specialties until they find the one who will be able to effectively help them manage their migraine. Additionally, they expressed concerns regarding the management of their disease due to patient-physician communication gap, dissatisfaction with traditional oral preventive therapies and lack of therapeutic options for older ages and in case of existence of specific comorbidities.ConclusionParticipants agreed that Migraine has a multifaceted impact on several aspects of patients’ lives. Patient-centered care, better training for healthcare providers, targeted therapies, and improved communication tools emerged as key factors in addressing the unmet medical needs of migraine sufferers.